Microwave-Assisted Synthesis of Metalloporphyrins - Singh, Ram; Geetanjali (Asian Journal of Chemistry, 2016)
A clean and eco-friendly microwave-assisted metallation of different free base 5,10,15,20-tetraarylporphyrins (TAP) in 84 to 92% yields is described under dry reaction conditions.